Improving Reading Comprehension Through Cooperative Integrated Reading and Composition: Meningkatkan Pemahaman Membaca Melalui Pembelajaran Membaca dan Penulisan Terpadu Berbasis Kerja Sama - Ilham Syaputra; Apdoludin Apdoludin; Reni Guswita (Academia Open, 2025)
General background: Reading comprehension is a fundamental skill that significantly influences students’ academic success, yet many elementary learners still face challenges in developing it effectively. Specific background: In Indonesian primary schools, conventional teaching methods often limit students’ active engagement, thereby reducing opportunities for deeper comprehension. Knowledge gap: Limited empirical studies have examined the effectiveness of Cooperative Integrated Reading and Composition (CIRC) in enhancing reading comprehension within this context. Aims: This study aimed to investigate the impact of the CIRC approach on improving reading comprehension among fourth-grade students at SDN 100/II Muara Bungo during the odd semester of 2025/2026. Results: Conducted as a two-cycle classroom action research with 28 participants, findings showed progressive improvement: teacher activity increased from 85% in cycle I to 95% in cycle II, student activity from 64% to 96%, and reading comprehension achievement from 75% to 92%. Novelty: The study highlights the adaptability of CIRC in Indonesian elementary settings, demonstrating its ability to foster both active participation and comprehension. Implications: These findings suggest that integrating CIRC into reading instruction can significantly enhance learning outcomes, offering educators an effective pedagogical model for strengthening literacy skills in primary education. Highlights: CIRC significantly improved students’ reading comprehension. Teacher and student activity increased across cycles. The approach is adaptable to Indonesian elementary schools. Keywords: Cooperative Reading, Reading Comprehension, Action Research, Elementary Education, Student Engagement